Phytochemical Screening, Phenolic Compounds and Antioxidant Activity of Biomass from Lychnis flos-cuculi L. In Vitro Cultures and Intact Plants - Maliński, Michał P. (Plants (Basel), 2021)
Lychnis flos-cuculi L., a species with potential medicinal value, contains flavonoids, phenolic acids, triterpenoid saponins and ecdysteroids. In this study, the antioxidant activity of plant material of L. flos-cuculi obtained from in vitro cultures compared to that of intact plants from the natural site has been evaluated for the first time. Phytochemical screening of the in-vitro-derived material by ultra-high-performance liquid chromatography mass spectrometry (UHPLC-MS) confirmed the presence of the aforementioned metabolite classes. The aqueous methanolic extracts from in-vitro-derived plant material and the organs of intact plants were analyzed using spectrophotometric methods to quantify total phenolics, phenolic acids and flavonoids, and determine the preliminary antioxidant activity by ferric reducing antioxidant potential (FRAP) and DPPH radical scavenging activity assays. The results showed that the inflorescence (Ns-F), and flowering herb of both plants gathered from natural habitat (Ns-H) and in-vitro-derived plants from the experimental plot (ExV-H) are the materials richest in polyphenols (195.4, 113.47, 112.1 mg GAE g(−1) d.w., respectively), and demonstrate the highest antioxidant activity (20.14, 11.24, and 11.46 mg AAE g(−1) d.w.). The extract from callus exhibited the lowest polyphenol content and antioxidant potential. The contents of total phenolics, flavonoids and phenolic acids correlate with the results of the antioxidant capacity of L. flos-cuculi extracts.